The Impact of Online Advertising Through Instagram Social Media on Product Purchase Decisions in Yogyakarta - Telaumbanua, Tomo Saro; Purnomo, Hadi; Kaloeti, Ade Kristianus (Universitas Kristen Immanuel, 2021)
This study aims to determine the profile of respondents on the influence of online advertising through social media Instagram on product purchasing decisions in Yogyakarta. The next objective is to determine the profile of respondents and the effect of online advertising partially and simultaneously on product purchasing decisions in Yogyakarta by using variables attention, interest, desire. This study uses a quantitative approach, namely research conducted to determine the value of a variable. The population in this study is the number of all users who use social media Instagram in Yogyakarta. In this study, the authors used primary data through respondents. This research was conducted by taking primary data from respondents who had filled out distributed questionnaires. In this study, the authors collected data through a questionnaire, the data collected were 100 questionnaires filled out by respondents who used social media Instagram to shop online. The analytical tool used is percentage analysis, simple linear analysis which is supported by t test and multiple linear supported by the F test. The results of the percentage analysis show that the highest percentage of Instagram social media users are mostly women, aged 18-25 years. , tertiary education (S1), Student / Student work, income ? Rp. 2.500.000.00. Based on the influence of the variable attention, interest, desire partially using simple linear regression analysis and t test, it shows the effect of online advertising advertising with the variable attention, interest, desire on purchasing decisions. Based on the influence of attention, interest, desire variables simultaneously using multiple linear regression analysis and the F test, it shows that F counts 21.287> F table 2.70, meaning that simultaneously has a significant effect on product purchasing decisions in Yogyakarta.